Stilbene monomer glucoside isolated from Vatica Odorata (Dipterocarpaceae) / Wan Zuraida Wan Mohd Zain … [et al.] - Wan Mohd Zain, Wan Zuraida; Daud, Shaari; Latip, Jalifah; Maolana Syah, Yana; Ahmat, Norizan (Universiti Teknologi MARA Cawangan Pahang, 2008)
An acetone extract of Vatica odorata was examined as a part of an ongoing search for much higher condensed stilbenoid In this paper, the structure elucidation of resveratrol-13-O-B-D-glucoside is discussed based on physical and spectroscopy analyses. Cytotoxic properties of the isolated compound was evaluated against murine leukimia P-388 cells and Artemia salina, resulting resveratrol-13-O-B-D- glucoside as inactice compound.